Women Workforce in Construction during the COVID-19 Pandemic: Challenges and Strategies (Construction Economics and Building, 2021)
Changes and challenges in employment are inevitable under the measures enacted to contain the COVID-19 pandemic. Early evidence suggests that the pandemic would disproportionately affect women compared to men. Focussing on women workforce in construction, this exploratory study examines the challenges associated with changes in their job situations, the adopted strategies in addressing the challenges and their opinions on employment situation of women workforce during the pandemic. Results of a content analysis show that the top ranked challenges are: (i) overworked; (ii) working space; (iii) social interactions; (iv) collaboration; and (v) parenting. The most cited strategies in addressing these challenges are: (i) increased visual communication; (ii) a dedicated workspace; (iii) self-scheduling; (iv) flexible working arrangements; and (v) breaking out work time and personal time. The evidence is suggestive that most challenges are interrelated, and the strategies adopted by the respondents are multi-level and interdependent. The results also show that the most mentioned opinion is the increased caring and domestic responsibilities among women workforce. Under the uncertainty about the duration of the pandemic and future contagion waves, these findings are critical in informing employing organizations’ human resource management challenges to better support their female employees during pandemic time and beyond.